Identification of immunohistochemical localization of irisin in the dwarf hamster (Phodopus roborovskii) tissues - Gur, F. M.; Timurkaan, S.; Tarakci, B. Gencer; Yalcin, M. H.; Ozkan, Z. E.; Baygeldi, S. B.; Eroksuz, H. (Wiley, 2018)
Irisin is mainly secreted by heart and skeletal muscle cells. It is an exercise-induced protein that converts white adipose tissue to brown. Increased irisin expression was lead to weight loss and improved glucose tolerance. We investigated irisin immunoreactivity in various tissues of the dwarf hamsters (Phodopus roborovskii). Tissues were processed, embedded in paraffin, sectioned at 5m and stained immunohistochemically for irisin. In the retina, irisin was found almost all layers, except outer nuclear layer. Also, irisin immunoreactivity was observed in the skin, cornea, striated muscle, parotid gland, tongue, oesophagus, stomach and small intestine. The findings from this study support the notion that skeletal muscle is not the primary source of irisin.
Keywords: cornea; irisin; retina; skin; small intestine; stomach; striated muscle